Experimental study on lodged corn harvest loss of small harvesters - Fu, Qiankun; Fu, Jun; Chen, Zhi; Cui, Shoubo; Ren, Luquan (International Journal of Agricultural and Biological Engineering, 2022)
The harvesting difficulty caused by corn lodging aggravated the loss of grain, especially in the regions where small harvesters were used as the main force for corn harvesting. An experimental study and analysis of harvest loss of small harvesters on the root lodged corn were made to get the laws of lodged corn harvest loss. The experiment was conducted in different harvesting directions and at a range of harvesting speeds. A 4-row self-propelled corn harvester (JM-4Y), a 2-row crawler type self-propelled corn harvester (JM-2C), and a 2-row crawler-type corn harvester equipped with a spiral auxiliary feeding device for lodged stalks (JM-2CAF) were taken as the research objects and the grain loss per square meter and the ear loss quantity per 30 square meters were taken as the experiment indices. The results showed that the average grain loss masses of the JM-4Y harvester, the JM-2C harvester and the JM-2CAF harvester in different harvesting directions were 101.88g, 285.72 g and 110.20 g, while the average corn ear losses were 10.08, 33.54 and 9.28 pieces. The lowest harvest loss of the JM-4Y harvester appeared when the harvesting was the same as the lodging direction, while the JM-2CAF harvester caused the lowest harvest loss when the harvesting direction was opposite to the lodging direction. The different feeding demands of the ordinary harvester head and the auxiliary feeding devices made the harvesters have different feeding conditions. At different harvesting speeds, the average grain loss mass of the JM-4Y harvester, the JM-2C harvester and the JM-2CAF harvester were 139.06 g, 453.42 g and 236.64 g while the average corn ear loss quantities were 15.12, 52.52 and 34.80 pieces. The JM-4Y harvester had the lowest harvest loss at almost every harvesting speed, and the JM-2CAF harvester only had lower harvest loss when the harvesting speed was lower than 0.8 m/s. The insufficient time to lift and deliver the lodged stalk and the impact between the spiral blades and the stalks were the causes of harvest loss when harvesting speed got higher. This study provides practical and theoretical references for the loss reduction of lodged corn harvesting. Keywords: corn, combine harvester, harvest loss, lodging, small harvester, experimental study DOI: 10.25165/j.ijabe.20221504.6745 Citation: Fu Q K, Fu J, Chen Z, Cui S B, Ren L Q. Experimental study on lodged corn harvest loss of small harvesters. Int J Agric & Biol Eng, 2022; 15(4): 123–129.